PENGARUH JARAK TANAM DAN INTERVAL WAKTU PENGENDALIAN GULMA TERHADAP PERTUMBUHAN KACANG PANJANG (Vigna sinensis L.) - Muhammad Riadh Uluputty (Jurnal Agroekoteknologi, 2014)
Increasing production of beans cultivation requires good technique. The market demand is also quite high. This study aims to determine the effect of plant spacing and weed control intervals on the growth and yield of beans has been implemented. The experiment was the spacing of 40 x 60 cm, 40 x 40 cm and 40 x 30 cm, and the time interval weed control is two weeks after planting, three weeks after planting, and four weeks after planting. Results showed that the spacing independently significant effect on the number, length and weight of pods plant beans, and not rely on weed control treatment intervals. A spacing of 40 x 60 cm gives results more pods, the pods are longer and heavier than the pod treatment spacing 40 x 40 cm and 40 x 30 cm.